ANALISIS PERMINTAAN DAN PENAWARAN “SULAMAN SUJI” INDUSTRI RUMAH TANGGA KECAMATAN AMPEK ANGKEK DI KABUPATEN AGAM - Wage Ummami (Ensiklopedia Education Review, 2019)
This study aimed to analyze the effect of (1) the demand and supply Embroidery Suji toward equilibrium prices of clothing materials embroidered suji District of Ampek Angkek Agam (2) the equilibrium price clothing materials Embroidery Suji, consumer income, prices of goods substitution, and the preference for deals clothes Embroidery Suji District of Ampek Angkek in Agam District (3) the equilibrium price suji embroidered clothing materials, production costs and an estimate of the future price significantly influence embroidered dress materials suji deals in District Ampek Angkek Agam. Sources of data are the primary data with the population are entrepreneurs Embroidery Suji many as 127 people (the supply side) and the buyer Embroidery Suji (the demand side). With a sampling technique Cluster Random Sampling been chosen samples for entrepreneurs Embroidery Suji were 96 people who terseber in Nagari Hall Gurah as many as 71 people, Lambah 11 people and 14 people. Meanwhile, on the demand side elected a sample of 96 people with accidental sampling technique. The study concluded that (1) Demand and supply Embroidery Suji significant effect on the equilibrium price embroidered dress materials Suji Agam District of Ampek Angkek. (2) Price balance Suji Embroidery clothing materials, consumer income, prices of goods substitution, and preferences significantly influence demand for embroidered garments Suji District of Ampek Angkek in Agam District. (3) Price balance Suji Embroidery clothing materials, production costs and an estimate of the future price significantly influence embroidered dress materials Suji deals in District Ampek Angkek Agam.